Pengaruh Corporate Social Responsibility terhadap Nilai Perusahaan dengan Earnings Management sebagai Variabel Mediasi - Prinintha Nanda Soemarsono; Bani Alkausar (Akuntansi : Jurnal Akuntansi Integratif, 2019)
The purpose of this study was to determine the ability of earnings management to be a mediating variable in the relationship between and corporate social responsibility to corporate value of the investor / prospective investors. The sample used in this study was 108 companies that entered the competition Indonesia Most Trusted Company between 2009 and 2014. Path analysis is used by researcher to determine direct and indirect effect between exogenous and endogenous variables in this study. Hypothesis testing is done using SPSS ver. 20. The results obtained in this study corporate social responsibility has a positive influence on the enterprise value, and earnings management has a negative effect on the enterprise value. Earnings management can not be a mediating variable in the relationship between corporate social responsibility with the enterprise value.